THE EFFECT OF TYPE OF FEED AND SLAUGHTER AGE ON THE PERFORMANCES AND CARCASS CHARACTERISTIC OF MALE ARAB CHICKEN - Suryanto, E.; Sasongko, H.; Maryam, M.; Santosa, R. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
An experiment was conducted to evaluate the effect of type of feed and slaughter age on the performancesand carcass characteristics of male Arab chicken. Thirty six male Arab chicken of seven weeks old weredivided into two groups, each group consisted of three cages with six chicken in each group. Two types ofration consisted of Ration One (Par-S + corn) containing 2904 kcal ME and 17 % CP, and Ration Two (BRII) containing 3100 kcal ME and 19% CP. The chicken were raised for seven weeks, weekly weighed, andrandomly taken for slaughter at 12 and 14 week old. The data collected were performances and carcasscharacteristics of the chicken. The data were analyzed using analysis of variance of completely randomiseddesign. The results showed that the chicken fed BR II consumed more protein and energy (483.7 g CP and7868.8 kcal ME) compared to the chicken fed BR I (444.0 g CP and 7586.1 kcal ME). Besides, the chickenfed BR II produced heavier final body weight (1142.5 g) than the chicken fed with BR I (1048.6 g) (P <0,05). Type of ration affected the tenderness of chicken. Slaughter age influenced carcass weight andcarcass physical composition of the chicken (P<0.05). Slaughter age affected the physical characteristic ofmeat. It could be concluded that male Arab chicken fed ration containing higher CP and ME (higher feeddensity) consumed more protein and energy, and finally had heavier final body weight. Slaughter age influencedcarcass weight, carcass physical composition and meat characteristics of the male Arab chicken.